Relationship Between Abnormalities on High-Resolution Computerized Tomography, Pulmonary Function, and Bronchoalveolar Lavage in Progressive Systemic Sclerosis - Cakmak, Gulfidan; Selcuk Can, Tuba; Gundogdu, Sule; Akman, Canan; Ikitimur, Hande; Musellim, Benan; Ongen, Gul (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Introduction and aim: Progressive systemic sclerosis (pSS) is a multisystemic connective tissue disease characterized by fibrosis of the skin and internal organs including lung. The mechanisms that leads to progressive lung fibrosis in scleroderma remain obscure. In this study, we aimed to investigate the correlation between HRCT findings and patients’ clinical and functional status and the degree of alveolitis based on the BAL resultsMaterials and methods: 65 patients with pSS were evaluated. Thoracic HRCT, pulmonary function tests, and dyspnea measurements were applied, and BAL was performed. The parenchymal abnormalities identified on HRCT were coded, and  scored according to Warrick et al.Results: Among parameters investigated, a correlation was found between the number of segments with subpleural cysts and the duration of disease. Also there was a correlation between the HRCT score and patient age whereas no correlation was detected between the duration of the disease, manifestation of the symptoms, and the x-ray findings. A correlation was found between the percentage of neutrophils detected in BAL and the extent of the honeycombing on HRCT.Conclusion: This study showed a strong correlation between the extent of x-ray abnormalities and FVC, RV, and DLCO, as well as an increase in the percentage of BAL fluid neutrophils in patients with SSc-PI.